Development service model of cockpit for flight simulator - Kolisnichenko, R.A. (Інститут програмних систем НАН України, 2017)
Methodology development service-resource model of IT-service is considered "Support functions for pilotage cockpit" flight simulator. The structure for flight simulator as totality of the hardwarily-programmatic embedded systems of the real time is presented that is incorporated by the ramified communication net. This structure of flight simulator is worked out for application of principles construction IT-infrastructure, as a methodological going near modernisation, extending of exploitation the hardwarily-programmatic providing for the real flight simulators, and also for development of new flight simulators. Determination over of IT-service for pilotage cockpit is brought. Development of service-resource model for IT-service is executed "Support functions for pilot-age cockpit".This methodology allows effectively to use the information and telecommunication resources of flight simulator, perfect information-calculating processes, provide optimal cooperation ideological and technological separate subsystems of cabin of flight simulator, to promote reliability of all flight simulator and return from capital investments.